Studi Populasi Owa Jawa (Hylobates moloch) di Lereng Gunung Slamet Jawa Tengah - Sri Wahyuni; Erie Kolya Nasution (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2016)
Javanese Gibbon (Hylobates moloch) is the endemic primate species in Indonesia. IUCN - World Concervation has given this species an endangered status. The habitat Hylobates moloch’s were found at Slamet Mountain in Central Java. The study entitled "Study of Javanese Gibbon (Hylobates moloch) Population in Slopes of Slamet Mountain, Central Java" aimed to determine the number of population in slopes of Mount Slamet. This research was conducted in the exact line these July -November 2013, the survey method with stratified sampling base on line transect method was used in this research. Transects pathway in this study used existing pathways wich the passed and cut the contour of research sites. Javanese Gibbon (Hylobates moloch)  obtained along the transect was calculated and analyzed using perpendiculars distance approach (DISTANCE 5.0’s software). Analysis by DISTANCE 5.0 showed that the density of Javanese Gibbon (Hylobates moloch) at Slamet Mountain in 170 km2 area was 0.26 individual/km2, coefficient of variation was 34.88 % , lower limit of 95 % confidence interval was 0.13365 to 0.51981. Based on the analysis, total number of javanese gibbon population at Slamet Mountain was 45 individuals of the density 0.26 individuals/km2.